ANTI-INFLAMMATORY ACTIVITY OF AQUEOUS EXTRACTS OF GRACILARIA - K., CHALINI; M., JOHNSON; G., ADAIKALARAJ; GEORGE, VIDYARANI; P., RAMAKRISHNAN (International Journal of Current Pharmaceutical Research, 2017)
Objective: In the present investigation an attempt was made to examine the anti-inflammatory potential of aqueous extracts of Gracilaria salicornia C. Ag., Gracilaria edulis (Gmelin) Silva, Gracilaria corticata J. Ag., Gracilaria fergusonii J. Ag.,and Gracilaria verrucosa (Hudson) Papenfus from Mandapam, Gracilaria edulis (Gmelin) Silva., Gracilaria verrucosa (Hudson) Papenfus from Pulicate Lake, Gracilaria fergusonii J. Ag., Gracilaria corticata J. Ag. and Gracilaria corticata J. Ag. var. cylindrica from Tuticorin using heat induced haemolysis of RBC. In addition, the present study is focused to reveal the locality specific anti-inflammatory activities of selected Gracillaria species. Methods: The fresh seaweeds were boiled with distilled water (1:20 W/V) for 2 h. The slurry was filtered through Whatman No. 41 filter paper and condensed. The semi-solid crude extracts were used for anti-inflammatory analysis. Results: An aqueous extracts of studied Gracilaria species were effective in inhibiting the heat induced haemolysis at different concentrations. The results showed the dose dependent protection. The percentage of anti-inflammatory activity of studied Gracillaria was varied from 43.81 to 95.55. The highest percentage (95.55%) of activity was observed in 250 Âµg/ml of G. edulis aqueous extracts. The anti-inflammatory activity of studied Gracillaria species at 250 Âµg/ml were as follows G. edulis (Mandabam)>G. corticata (Mandabam)>G. verucosa (Mandabam)>G. salicornia (Mandabam)>G. ferugosonii (Tuticorin)>G. ferugosonii (Mandabam)>G. edulis (Pulicate)>G. corticata (Tuticorin)>G. verucosa (Pulicate)>G. corticata var. cylindrica (Tuticorin). Conclusion: The results of the present study clearly explained the anti-inflammatory potential of the studied Gracillaria species. The aqueous 0extracts of Gracillaria collected from Mandapam showed the highest percentage of protection activity. This study results confirm the existence of active principle responsible for the anti-inflammatory activity. Further studies are required to isolate the active principles without any side effects.